Synthesis of magnetite nanoparticles using electrochemical oxidation - Ye. Ya. Levitin; I. D. Roy; O. S. Kryskiv; T. M. Chan (Zaporozhye State Medical University, 2014)
The monodisperse magnetite nanoparticles are promising for use in the biomedical industry for targeted drug delivery, cell separation and biochemical products, Magnetic Resonance Imaging, immunological studies, etc. Classic method for the synthesis of magnetite is the chemical condensation Elmore's, it is simple and cheap, but it is complicated by the formation of side compounds which impair the magnetic properties of the final product. Biological and medical purposes require high purity magnetite nanoparticles. Electrochemical methods of producing nanoparticles of magnetite acquire significant spread. The kinetics of electrochemical processes are a function of a larger number of parameters than the kinetics of conventional chemical reaction, thus electrochemical reactions can be thinner and more completely adjusted to give a predetermined size nanoparticles. In the kinetics of the electrochemical oxidation and reduction the important role is played by the nature of the electrode. In many industrial processes, it is advisable to use lead dioxide anodes with titanium current lead. Purpose of the work To determine the optimum conditions of electrochemical oxidation of Fe2+ Fe3+to produce magnetite with high purity and improved magnetic characteristics. Materials and methods Electrochemical studies were carried out in a glass cell ЯСЭ-2 using a potentiostat ПИ-50-1.1 and a recording device ПДА1. Reference electrode - silver chloride ЭВЛ1М 3.1, potentials listed on the hydrogen scale. The test solution contained 80 g/ l FeSO4×7H2O and H2SO4(to pH 1). The pH of the solution was measured with a pH-meter « рН-150». Concentration ratio of Fe3+/Fe2+in the solution was measured by permanganometric method. Magnetite particle sizes were measured by an electron microscope computer ЭВМ-100Л, an increasing is 2×105. Saturation magnetization was evaluated by the magnetization curve, for the measured sample in the field with strength of 800 kA/m. Measurements were performed using microwebermeter Ф191. Results and discussion On lead dioxide anode in an acidic solution of FeSO4 the basic process is the process of Fe2+- = Fe3+ oxidation. The rate of this process increases at potentials higher than 1.3V, which is associated with the passage adjacent the reduction reaction of water to oxygen. At potentials higher than 1.7V passage of process conditions is achieved: 3Н2О - = О3 + 6Н+, which is more energy intensive and therefore undesirable. To intensify the anodic process it is necessary to apply the mixing that reduces the thickness of the diffusion layer near the electrode and allows oxidation at a current density of 0.7-1.2 A/dm2. Under appropriate conditions of electrolysis (high current density of the cathode, acidification of the solution) loss of iron Fe2+ is avoided at the expense of cathodic discharge, as mainly at the cathode the reducing of cations H+ occurs. As the result of the electrolysis the solution containing Fe3++and Fe2+ (2:1) was obtained. After alkalization the precipitate Fe3O4i was formed. The particle size is 10 - 15 nm, the magnetic susceptibility is 1.18. On the basis of magnetite the experimental samples of magnetic fluid were synthesized. The saturation magnetization of the magnetic fluid is 35 kA/m. Conclusions 1. Electrochemical method of oxidation Fe2+ Fe3+ has been proposed using lead dioxide anode and the optimal conditions of electrolysis has been determined. 2. Obtained magnetite is of high purity and improved magnetic properties. It can be used to create new magnetically dosage forms.